2017
DOI: 10.3892/ijmm.2017.3330
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous hydrogen sulfide protects human umbilical vein endothelial cells against high glucose‑induced injury by inhibiting the necroptosis pathway

Abstract: Hyperglycemia is a key factor in the development of diabetic complications, including the processes of atherosclerosis. Receptor-interacting protein 3 (RIP3), a mediator of necroptosis, is implicated in atherosclerosis development. Additionally, hydrogen sulfide (H2S) protects the vascular endothelium against hyperglycemia-induced injury and attenuates atherosclerosis. On the basis of these findings, the present study aimed to confirm the hypothesis that necroptosis mediates high glucose (HG)-induced injury in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 38 publications
7
24
0
Order By: Relevance
“…56 In a recent research, it was demonstrated that exogenous H 2 S can effectively attenuate HG-induced multiple injuries in endothelial cells. 57 Consistent with previous studies, we observed in the present research that NaHS-treatment can distinctly reduce HG-induce cytotoxicity, apoptosis, oxidative stress and inflammation in HUVECs. The present study is the first to demonstrate that HG-triggered ER stress in HUVECs can be suppressed by treatment with exogenous H 2 S. There is a recent report showing that exogenous H 2 S can alleviate cardiovascular injury by inhibiting ER stress in diabetic rats, which is consistent with our observation.…”
Section: Dovepresssupporting
confidence: 94%
See 1 more Smart Citation
“…56 In a recent research, it was demonstrated that exogenous H 2 S can effectively attenuate HG-induced multiple injuries in endothelial cells. 57 Consistent with previous studies, we observed in the present research that NaHS-treatment can distinctly reduce HG-induce cytotoxicity, apoptosis, oxidative stress and inflammation in HUVECs. The present study is the first to demonstrate that HG-triggered ER stress in HUVECs can be suppressed by treatment with exogenous H 2 S. There is a recent report showing that exogenous H 2 S can alleviate cardiovascular injury by inhibiting ER stress in diabetic rats, which is consistent with our observation.…”
Section: Dovepresssupporting
confidence: 94%
“…The PI3K/AKT/eNOS pathway may be not the only pathway responsible for the protective role of NaHS on glucotoxicity, and necroptosis signaling has been shown to involve in the protective role of NaHS. 57 On the other hand, PI3K/AKT/eNOS pathway is an important signaling pathway for ER stress, ROS production, inflammation and apoptosis in endothelial cells. [61][62][63][64] LY294002 had no effects on the functions of the HUVECs, which is consistent with previous findings.…”
Section: Dovepressmentioning
confidence: 99%
“…Exposure to high glucose results in elevated ROS production and apoptosis, as well as decreased superoxide dismutase activity in endothelial cells, and all the above responses could be eliminated by pretreatment with H 2 S (Guan et al, 2012). Exogenous H 2 S alleviated the ROS overproduction and apoptosis in hyperglycemic endothelial cells through inhibiting necroptosis (Lin et al, 2018). In the aortas of diabetic rats, the connexin (Cx) 43 and 40 expressions are downregulated, while protein kinase C (PKC) and nicotinamide adenine dinucleotide phosphate-oxidase (NADPH) oxidase subunits are upregulated, H 2 S appears to be effective in attenuating these abnormalities (Zheng et al, 2010).…”
Section: H 2 S-related Endothelial Dysfunction In Diabetic Vascular Cmentioning
confidence: 99%
“…Endothelial dysfunction is a vital event event in the early stages of atherosclerosis ( Peng et al, 2017 ). Hyperglycemia is a key factor in the development of diabetic complications, such as atherosclerosis ( Lin J. et al, 2018 ). Receptor interacting protein 3 (RIP3) mediates necrotic apoptosis and is involved in the development of atherosclerosis.…”
Section: H 2 S and Cardiovascular Diseasesmentioning
confidence: 99%
“…Receptor interacting protein 3 (RIP3) mediates necrotic apoptosis and is involved in the development of atherosclerosis. NaHS significantly attenuated high-glucose (HG)-induced apoptosis of HUVECs by inhibiting the expression of RIP3 ( Lin J. et al, 2018 ). NaHS also reduces atherosclerotic plaque in rats by protecting vascular endothelial cells and reducing the production of aortic endothelium ET-1 ( Li et al, 2015d ).…”
Section: H 2 S and Cardiovascular Diseasesmentioning
confidence: 99%